Diabetes care: a time to review prescribing approaches and reach out to local communities. (2nd May 2021) - Phillips, Anne
Abstract : Diabetes care has undergone a rapid change in delivery since the first lockdown from COVID-19 in March 2020. As such, services have had to reshape and transform into virtual diabetes reviews. Vulnerable communities with high diabetes incidence or risk have experienced health disparities, not least because of COVID-19, but also as a result of slower medication reviews and escalation of diabetes prescribing as required. This article critically examines the presenting inequalities in diabetes care provision in the UK. In particular focusing on the experience of minority ethnic populations, who experience inequality and health disparities, especially related to prescribing of newer medications in type 2 diabetes. Evidence from studies and reports underpins the debates presented about reconsidering diabetes care delivery and in particular listening to and working with local practices and their communities to disseminate health messages and provide person-centred educational opportunities.